Andreev experiments on superconductor/ferromagnet point contacts - Bouvron, S.; Stokmaier, M.; Marz, M.; Goll, G. (Физика низких температур, 2013)
Andreev reflection is a smart tool to investigate the spin polarization P of the current through point contacts
between a superconductor and a ferromagnet. We compare different models to extract P from experimental data
and investigate the dependence of P on different contact parameters.